Reconsidering Thornton v. Caldor - Christopher C. Lund (Washington University Law Review, 2020)
Thirty-five years ago, the United States Supreme Court decided Estate of Thornton v. Caldor. Caldor struck down, on Establishment Clause grounds, a Connecticut statute giving employees the right not to work on their chosen Sabbath. Caldor was the first Supreme Court case to impose constitutional limits on religious exemptions, and is constantly invoked and debated in modern disputes over free exercise. Yet Caldor also contains curiosities and mysteries. The Court’s opinion is short, its holding unclear, and its reasoning somewhat incomplete. This short symposium piece takes a look back at Thornton v. Caldor, seeking to offer a clearer discussion of this famously muddy case. Placing the case in historical context, it takes a deeper dive into the Court’s decision—scrutinizing what the Court said and reflecting on what it left out.
Keywords: Thornton v. Caldor 462 U.S. 703 (1985); First amendment; Establishment clause; Free exercise; Sunday closing laws